Constituents of the Essential Oils of Two Hypericum capitatum Choisy Varieties (var. capitatum and var. luteum Robson) from Turkey - Bagci, Eyup; Yuce, Ebru (Taylor & Francis Ltd, 2011)
The essential oils from the aerial parts of two varieties (var. capitatum and var. luteum Robson) of Hypericum capitatum (Sect. Drosanthe) grown in Turkey were analyzed by GC and GC-MS. Forty-eight compounds were identified in the essential oils of var. capitatum with alpha-pinene (20.3 %), caryophyllene oxide (11.8 %), hexadecanoic acid (8.9 %), beta-caryophyllene (6.5 %) and undecane (3.8 %) as main constituents. Thirty-eight components were identified in the oil of var. luteum with camphor (15.3 %), germacrene D (10.5 %), beta-myrcene (7.4 %), caryophyllene oxide (6.5 %) and beta-cububene (6.3 %), as the abundant components. More quantitative and qualitative differences were determined between two varieties of H. capitatum essential oils. The results were discussed in means of renewable resources and chemotaxonomy.
Keywords: Hypericum capitatum; GC-MS; Essential oil; alpha-pinene; camphor; chemotaxonomy